Specification of blood meals ingested by female sand flies caught in Palestinian foci and identification of their concomitant leishmanial infections. - Kifaya Azmi; Gabriele Schonian; Ziad Abdeen (Public Library of Science (PLoS), 2020)
Since leishmaniases are zoonotic vector-borne diseases transmitted through the bites of infected female sand flies, identification of the sources of imbibed blood meals and the detection and identification of leishmanial DNA in them are important in discerning animal reservoirs, clarifying the epidemiology and facilitating control of local leishmaniases. CDC light traps, aspirators and sticky paper traps were used to collect sand flies in four Palestinian foci of both, CL and VL. Phlebotomine species identification was based on morphological keys. Female specimens were screened to detect and identify leishmanial infections, using kDNA-PCR and ITS1-PCR, and engorged female specimens were analyzed to identify the origin of their blood meals, using an RDB blood meal assay based on the amplification of the cytochrome b gene (cytb) of vertebrate mitochondrial DNA (mtDNA). Twenty sand fly species, 11 of the genus Phlebotomus and nine the genus Sergentomyia, were identified. The most abundant species was Ph. papatasi (33.7%), followed by Ph. sergenti (21%). Among the 691 female sand fly specimens, 18.5% (128/691) were positive for leishmanial DNA, using the kDNA-PCR and 6.4% (44/691) were positive using the ITS1-PCR. DNA from parasites of the genus Leishmania was identified in only 1.5% of the infected sand flies. That of Leishmania tropica parasites was detected in six female specimens of Ph. sergenti and that of L. major parasites in two female specimens of Ph. papatasi. Interestingly, two engorged females of the species Se. (Neophlebotomus) sp. were positive for L. tropica DNA. Ninety engorged female sand flies of Ph. papatasi and 104 of Ph. sergenti had fed on a large variety of vertebrate hosts such as humans, hyraxes, rats, cows, goats and birds. Regarding blood-meals showing a mixture from different species of animal host, hyrax and rat blood was revealed in 8/104 (7.7%) females of Ph. sergenti. Detection of hyrax blood in engorged female sand flies of the species Ph. sergenti supports the role of hyraxes being a potential reservoir of L. tropica in Palestinian regions. Rat blood meals might be significant since a few strains L. tropica and L. infantum were isolated from rats. Further studies must be undertaken before conclusions could be drawn.